Analisis karakteristik rumah tangga miskin di wilayah pusat Kota Makassar Provinsi Sulawesi Selatan - Bastiana Bastiana; Najamuddin Najamuddin; Rusman Rasyid (Seminar Nasional LP2M UNM, 2019)
This paper aims to present an analysis of the characteristics of poor households in the downtown area of Makassar which was collected through observation, in-depth interviews with informants in 98 households as samples. The results of this study indicate that in terms of demographic characteristics, generally poor households in Makassar City have male heads of age aged ≤ 50 years, have a household membership of > 4 people and are indigenous. In terms of economic characteristics, generally poor households have income of ≤ IDR. 600,000 per month so that it does not have assets that are easily sold, has the ability to provide food ingredients ≤ 2 times a day, buy meat and milk ˂ 1 time a week, is unable to pay medical expenses if there is a family member who is sick, and is only able to buy new clothes ≤ 1 time in a year even then just before the religious holiday. In addition, the poor people also use the type of gas fuel for daily cooking due to the subsidized gas from the government through the kerosene to gas compression program. Judging from social characteristics, generally poor households have a low level of education, i.e. no school (TS), do not finish elementary school (TTSD), graduate from elementary school (SD) and finish junior high school (SMP). In terms of health, the poor generally have MCK facilities but they only consume drinking water from PDAMs such as in the downtown area even though they have to buy. Judging from the characteristics of housing, generally poor households have semi-permanent or emergency housing, this can be seen from the number of houses that have a floor area of ≤ 8 square meters per person with the type of flooring made of low quality soil or wood, and having a type of wall made from non-wall materials such as low quality wood, zinc, plywood and others as well as lighting sources using electricity.